BMKG'S DISASTER COMMUNICATION STRATEGY ON INSTAGRAM: A MEDIA ECOLOGY ANALYSIS OF THE @infobmkgsumut ACCOUNT - Ramzy Ikram; Faisal Riza (Program Pascasarjana UIN Sumatera Utara, 2026)
This study analyzes the BMKG's disaster communication strategy through the Instagram account @infobmkgsumut using the perspectives of media ecology and the social construction of reality. This study is motivated by the importance of delivering disaster information quickly, clearly, and easily understood by the public, especially in the context of North Sumatra, which is vulnerable to extreme weather, tidal flooding, hydrometeorological disasters, and seismic activity. This study uses a descriptive qualitative method with data collection techniques through observation of Instagram content, documentation of posts, and interviews with six informants from the Asahan, Pematang Siantar, Langkat, Deli Serdang, and Medan regions. The results show that @infobmkgsumut constructs risk through early warnings, infographics, reels, press releases, weather symbols, regional markers, event periods, and awareness narratives. Disaster risk is not only conveyed as technical data, but is packaged as a social reality that needs to be understood and responded to preventively. Public acceptance of disaster messages is influenced by visual clarity, regional relevance, local experience, and the ease of information being applied in daily activities. This study concludes that Instagram acts as a media ecology that shapes how disaster messages are produced, visualized, received, and internalized by the public.